Financial Literacy, Financial Behavior, and Financial Inclusion as Critical Determinants of Economic Resilience Among Fishing Families in Tambak Lorok, Semarang, Indonesia - Kamiliya Nurul Karomah; Inaya Sari Melati (Manunggal Halim Jaya, 2026)
Tanjung Mas is an administrative village in North Semarang that includes a fishing settlement known as Tambak Lorok, located within the Semarang Port area. Due to its direct access to the sea, the area is rich in marine resources. However, this abundance has not translated into prosperity for the local fishing families. In fact, Tanjung Mas is one of the three urban villages in Semarang City that are classified as experiencing extreme poverty. This condition has significantly impacted the area's economic resilience of fishing families. This study aims to analyze the influence of financial literacy, financial behavior, and financial inclusion—three factors that play an important role in determining the economic resilience of fishing families in Tambak Lorok. This research adopts a quantitative approach using a questionnaire-based survey method. Data analysis was conducted using SPSS version 26, chosen for its ability to objectively and empirically test the partial and simultaneous effects of independent variables on a single dependent variable. A total of 265 respondents were selected using a convenience sampling technique. The analytical method employed was multiple linear regression. The hypothesis testing results show that all three variables have a significant positive effect, with significance values of Sig. = 0.002 for financial literacy, Sig. = 0.001 for financial behavior, and Sig. = 0.000 for financial inclusion. Future research is encouraged to broaden the geographic scope of the study to enable comparative analyses across different fishing communities, adopt a mixed-methods approach for more comprehensive results, and consider modifying or adding other relevant variables.